Covid-19 antigen testing: better than we know? A test accuracy study. Issue 9 (2nd September 2021) - Homza, Miroslav; Zelena, Hana; Janosek, Jaroslav; Tomaskova, Hana; Jezo, Eduard; Kloudova, Alena; Mrazek, Jakub; Svagera, Zdenek; Prymula, Roman
Abstract: Background: Antigen testing for SARS-CoV-2 is considered to be less sensitive than the standard reference method – real-time PCR (RT-PCR). It has been suggested that many patients with positive RT-PCR 'missed' by antigen testing might be non-infectious. Methods: In a real-world high-throughput setting for asymptomatic or mildly symptomatic patients, 494 patients were tested using RT-PCR as well as a single lateral flow antigen test (Ecotest, AssureTech, China). Where the results differed, virus viability was evaluated by cell culture. The test parameters were calculated with RT-PCR and RT-PCR adjusted on viability as reference standards. Results: The overall sensitivity of the used antigen test related to the RT-PCR only was 76.2%, specificity was 97.3%. However, 36 out of 39 patients 'missed' by the antigen test contained no viable virus. After adjusting on that, the sensitivity grew to 97.7% and, more importantly for disease control purposes, the negative predictive value reached 99.2%. Conclusions: We propose that viability testing should be always performed when evaluating a new antigen test. A well-chosen and validated antigen test provides excellent results in identifying patients who are shedding viable virus (although some caveats still remain) in the real-world high-throughput setting of asymptomatic or mildly symptomatic individuals.